Renal function and arterial pressure changes induced by odontological short term therapy nonsteroidal anti-inflammatory drugs - Rodríguez Alfaro, Miguel Óscar (2007)
The aim of the study was to evaluate the possible modifications in the arterial pressure, corporal weigh and creatinine cleareance in urine gathered during 24 hours, in healthy young people, under therapy with two non steroidal anti inflammatory drugs (NSAID’s); one of them not selective to Ciclooxigenase (Ibuprofen) and a selective inhibitor of Ciclooxigenase - 2 (Celecoxib), during three days in standardized dose, in comparison with a control group that was administered placebo, in a double blind study. The results indicate that there are not statistically significant differences among the three groups, for the clinical and laboratory evaluated parameters (p <0,05). We conclude that a short term therapy with the used NSAID’s doesn’t produce clinical impact modifications in the arterial pressure, corporal weigh and creatinine cleareance in urine gathered during 24 hours.